1999
DOI: 10.1097/00005344-199902000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Inter- and Intraventricular Electrical Dispersion to Arrhythmogenesis in Normal and Ischaemic Rabbit Myocardium: A Study with Cromakalim, 5-Hydroxydecanoate and Glibenclamide

Abstract: This study aimed to investigate the role of electrical dispersion in arrhythmogenesis by using K(ATP) channel modulating agents. Monophasic action-potential duration (MAPD90), effective refractory period (ERP), and conduction delay were measured at three ventricular sites in isolated working rabbit hearts. Cromakalim (10 microM), glibenclamide (3 microM), or 5-hydroxydecanoate (100 microM) were administered before and throughout 30 min of regional ischaemia and 15 min of reperfusion. Before ischaemia, cromakal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…), a difference which is attributed to the greater expression of I K1 , the inward rectifier K + current, in LV cells . In rabbit heart, the published data on interventricular difference in repolarization are quite inconclusive, with APD shown to be similar in both ventricular chambers, or to exhibit a greater value in either RV or LV myocytes …”
Section: Spatial Repolarization Gradientsmentioning
confidence: 99%
“…), a difference which is attributed to the greater expression of I K1 , the inward rectifier K + current, in LV cells . In rabbit heart, the published data on interventricular difference in repolarization are quite inconclusive, with APD shown to be similar in both ventricular chambers, or to exhibit a greater value in either RV or LV myocytes …”
Section: Spatial Repolarization Gradientsmentioning
confidence: 99%
“…It should be noted, however, that in these animals glibenclamide significantly reduced both the exercise-and reactive-hyperemia-induced increases in coronary blood flow as well as depressed ventricular function (large reductions in left ventricular dP/dt maximum) [Billman et al, 1993[Billman et al, , 1998]. In the isolated working rabbit heart, glibenclamide provoked an immediate decrease in coronary blood flow, reducing forward flow to zero [Wolk et al, 1999]. Thus, glibenclamide has potent vasoconstrictor effects because of the inhibition of ATP-sensitive potassium channels located on the coronary vascular smooth muscle.…”
Section: Atp-sensitive Potassium Channel Antagonists: Ischemia-selectmentioning
confidence: 99%
“…When K ATP channels open during ischaemia, resultant dispersion of refractoriness and slowing of conduction could predispose to reentrant arrhythmias; by preventing these effects, K ATP channel blockade could be anti-arrhythmic and protective. In fact, some studies have indicated that K ATP channel blockers reduce the propensity for ischaemic arrhythmias [12,13], while K ATP channel openers facilitate induction of ventricular fibrillation [14][15][16].…”
Section: Introductionmentioning
confidence: 99%